2016
DOI: 10.3390/su8070681
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Efficiency of Small-Scale and Bottom Trawler Vessels in Greece

Abstract: This study explores the technical and scale efficiency of two types of Greek fishing vessels, small-scale vessels and bottom trawlers, using a bias-corrected input-oriented Data Envelopment Analysis model. Moreover, the associations between efficiency scores and vessel's and skipper's characteristics are also explored. The results indicate that small-scale vessels achieve a very low average technical efficiency score (0.42) but a much higher scale efficiency score (0.81). Conversely, bottom trawlers achieve lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 28 publications
(36 reference statements)
0
25
1
Order By: Relevance
“…Further, the high cost of inputs, bad weather and activities of trawlers were the most important limitations faced by the artisanal fisheries. In another study, Pinello et al () assessed small‐scale and bottom trawler vessels in Greece, finding the technical efficiency of small‐scale vessels, unlike trawlers, is positively related to the experience of the skippers. Similarly, Thean, Latif, and Hussein () examined the technical efficiency and factors causing inefficiency of sampled trawl vessels in Penang Malaysia using a DEA method.…”
Section: Methodsmentioning
confidence: 99%
“…Further, the high cost of inputs, bad weather and activities of trawlers were the most important limitations faced by the artisanal fisheries. In another study, Pinello et al () assessed small‐scale and bottom trawler vessels in Greece, finding the technical efficiency of small‐scale vessels, unlike trawlers, is positively related to the experience of the skippers. Similarly, Thean, Latif, and Hussein () examined the technical efficiency and factors causing inefficiency of sampled trawl vessels in Penang Malaysia using a DEA method.…”
Section: Methodsmentioning
confidence: 99%
“…The TI model showed that fishing experience and kinship ties were main factors that enhanced TE. The significance of fishing experience underscores the importance of fisher skill over fishing technology, which has been also reported in other small-scale fisheries (Oliveira et al 2016;Pinello et al 2016). Although fishing experience was expected to improve TE, we were uncertain how kinship relationships among the crew would influence efficiency.…”
Section: Variablementioning
confidence: 83%
“…Moreover, Oliveira et al (2016) observed that the use of social variables to analyze the performance of small-scale fleets has been fairly limited in the literature due to the absence of detailed data. Our study also contributes to a small but growing body of literature examining factors that affect the TE of smallscale fisheries (Fousekis and Klonaris 2003;Squires et al 2003;Esmaeili 2006;Sesabo and Tol 2007;Akanni 2010;Oliveira et al 2010Oliveira et al , 2016Pinello et al 2016).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The fishing fleets of these four countries were analyzed in this paper. All of the fleets were managed through input controls [21,22], largely based on fixed licence availability, temporal and/or spatial limitation, limits on the allowable gear types and-aside from for Bluefin tuna-without quota systems in place [6,7,[23][24][25]. In the Mediterranean there is not a single policy context, but rather a mix of international, regional and national policies are applied.…”
Section: Regional Background and Policy Contextmentioning
confidence: 99%